A New Filling Material for Cold Sleeve - Novak, Pavol; Zmindak, Milan (Communications - Scientific Letters of the University of Zilina, 2012)
The aim of this paper is to review material properties of a new filling material for cold sleeve. The first experimental measurements were performed on samples to determine required material properties. Then the structural analysis was performed for a pressurized pipe with insufficiently welded root and installed cold sleeve. The case of depressurized pipes that could cause a breach of cohesion between the filling material and surface of pipe or sleeve with the usage of cohesive finite elements was simulated.
Keywords: repairing pipes; cold sleeve; stress of welded joint; cohesive finite elements